Persepsi Orang Tua dengan Profesi Petani Karet Terhadap Pendidikan Bagi Anak di Desa Pampanan, Kecamatan Pugaan, Kabupaten Tabalong - Rabiah Rabiah; Ria Susanti (Madrasah: Jurnal Pendidikan Madrasah, 2024)
Perception is the brain's ability to translate incoming stimuli into the human sense organs. In perception there will be different points of view in sensing. There are those who perceive something as positive, there are also those who perceive something as negative, which will influence visible or real human actions. This research aims to explain the perceptions of parents with rubber farming professions regarding children's education. The method used in this research is a qualitative method which is presented descriptively. Descriptive research is a form of research aimed at describing existing phenomena, both natural phenomena and man-made phenomena. The results of the research show that each parent's perception is different, where the majority of parents with the rubber farmer profession perceive that their children only need to go to school up to high school level, while a small number of parents with the rubber farmer profession give their children the freedom to go to school. as high as possible.